THE ROLE OF JOB SATISFACTION INFLUENCING GENERATION Z TURNOVER INTENTION WITH ORGANIZATIONAL SUPPORT AND WORK LIFE BALANCE AS SUPPORTING FACTORS - Anwar, Syaiful (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This study aims to explore the effect of organizational support and work-life balance on job satisfaction and turnover intention, considering the role of gender as a moderating variable, among alumni of Budi Luhur University who have worked experience of at least one year. This study uses quantitative research and Cochrane formula sampling obtained by at least 96 people, but the author collected 120 respondents, where data were collected from alumni by distributing questionnaires online through a digital survey platform (Google Forms). Furthermore, the data obtained were analyzed using Structural Equation Modeling (SEM). The results showed that organizational support and work-life balance both had a significant effect on job satisfaction in alumni of Budi Luhur University, indicating that organizational support and balance between work and personal life can increase their job satisfaction. However, organizational support and work-life balance did not have a significant effect on turnover intention. In addition, job satisfaction was shown to have a significant effect on turnover intention, meaning that alumni who were satisfied with their jobs tended to have a lower intention to change jobs. Finally, gender was not shown to moderate the effect between job satisfaction and turnover intention.